2019
DOI: 10.1111/jfbc.13022
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the supplementation of açai lump flour in the diet of laying hens on productive performance, and fatty acid profiles and antioxidant capacity in the fresh and stocked eggs

Abstract: The aim of this study was to evaluate whether the supplementation with açaí flour in the feed of laying hens at the end of the production cycle has beneficial effects on the health and performance of the birds and on the quality of the eggs. Groups received basal diets supplemented with 0%, 0.25%, 0.5%, 1.0%, and 2.0% açaí lump flour. We observed better productivity linked to oviposition and egg mass in a dose‐dependent manner. We also observed higher shell resistance in stored eggs and higher % albumen and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Literature data revealed that much attention has been given to the application of different feed additives to improve performance and, the quality of freshly laid eggs, showing that limited data are available on the effects of antioxidants in the diets of laying hens and on the preservation of egg quality during storage. Other natural antioxidants of plant origin, like green tea, rapeseed oil, acai lump, pumpkin seeds, and natural astaxanthin [ 22 , 71 , 74 , 75 , 76 ], were very effective in preserving the shelf-life of eggs, including albumen and yolk quality during storage at different times and temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data revealed that much attention has been given to the application of different feed additives to improve performance and, the quality of freshly laid eggs, showing that limited data are available on the effects of antioxidants in the diets of laying hens and on the preservation of egg quality during storage. Other natural antioxidants of plant origin, like green tea, rapeseed oil, acai lump, pumpkin seeds, and natural astaxanthin [ 22 , 71 , 74 , 75 , 76 ], were very effective in preserving the shelf-life of eggs, including albumen and yolk quality during storage at different times and temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…as observed byFortuoso et al (2019) in egg yolks of laying hens supplemented with açai flour. According to Bezerra et al (2016), polyunsaturated and monounsaturated fatty acids protect cells and improve animal health, as do the fatty acids found in açai that improve animal health via their anti-inflammatory and antioxidant properties.…”
mentioning
confidence: 56%
“…The antioxidant mechanisms of flavonoids assist in the extinction or elimination of free radicals, as well as inhibition of the formation of enzymes that generate reactive oxygen species(Kang et al, 2011;Packer & Luz, 2007). LPO levels were also lower in the treatments that contained the highest levels of açai oil (T3 and T6), as observed byFortuoso et al (2019) in egg yolks of laying hens supplemented with açai flour. According toBezerra et al (2016), polyunsaturated and monounsaturated fatty acids protect cells and improve animal health, as do the fatty acids found in açai that improve animal health via their anti-inflammatory and antioxidant…”
mentioning
confidence: 95%
“…In layers, the beneficial health effects of different flours have been studied, such as açai flour (Euterpe oleaceae) or grape pomace flour. Those flours contain phenolic compounds and anthocyanins that have antioxidant effects, as well as a high content of lipids, proteins and fibre [12,13]. In order to compensate for the lack of fibre and antioxidant compounds in biscuit flour, FDA was also administered.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with certain enzymes, such as xylanase, these flours have proved to be useful for improving diet efficiency and egg quality parameters [5,11]. Moreover, certain types of flour can promote greater productive efficiency and stimulate the antioxidant defence mechanism system, improving the immune response and, therefore, inducing beneficial properties for animal health in laying hens [12,13].…”
Section: Introductionmentioning
confidence: 99%